PROCESSING AND CHARACTERIZATION OF LOW-VOLTAGE VARISTORS - Cerri, J. A.; Steil, M. C.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Belgian Ceramic Society, 1994)
ZnO seed particles and Cr2O3 were used in this study to control the microstructure of ZnO varistors. The seed particles were prepared by adding 1.0 mol % BaO to ZnO. The powder was then calcined at 800-degrees-C for 2 h, pressed into pellets and sintered at 1400-degrees-C for 8 h. The sintered ZnO was ground and the BaO eliminated by washing in water. The remaining ZnO powder was classified into a size fraction ranging from 38 to 149 mum. The addition of a small amount (1 weight %) ZnO seed grains produces varistors with low breakdown voltages (7.6 V/mm) and an alpha coefficient of approximately 10. The addition of Cr2O3 stabilizes the spinel phase yielding a more homogeneous microstructure, but degraded electrical behaviour of the ZnO varistor.